Edukasi kesehatan gigi dan mulut untuk peningkatan kesehatan gigi anak sekolah dasar di Kayee Lhee Aceh Besar - Mardiah, Ainun; Nuraskin, Cut Aja; Reca, Reca; Salfiyadi, Teuku (Jurnal PADE: Pengabdian & Edukasi, 2025)
Based on the 2018 Basic Health Research (Riskesdas), more than 90% of early childhood children experience dental caries, but only a small proportion receive dental health services. The purpose of community service is to increase students' knowledge, skills, awareness, and motivation in maintaining dental and oral health. The program was implemented for four days involving 40 elementary school students. Activities included counseling on the importance of maintaining dental hygiene, demonstrations on how to brush teeth properly, counseling on the dangers of sweet foods, and motivation for regular dental check-ups. The results of the activity showed an increase in knowledge (85%), tooth brushing skills (72%), awareness of the dangers of sweet foods (65%), and motivation for regular dental check-ups (55%). Conclusion This activity shows that an interactive educational approach is effective in instilling habits of maintaining dental health from an early age.